I take this man - Frankel, Valerie (Little Black Dress, 2007)
What happens when you 'do' but he 'don't'? When Jersey Girl Penny Bracket is left standing at the altar by fiancé Bram Shiraz she doesn't quite know how to react. Her mother, Ester, on the other hand knows exactly what to do - track Bram down, knock him unconscious with a bottle of Dom Perignon and imprison him in the attic of her mansion. But Ester's got some serious questions for the fugitive groom...plus she needs someone to write all the return labels for the wedding gifts. But can she find out why Bram got cold feet before everyone else discovers what she's done?